KOMUNIKASI PARIWISATA DINAS PENDIDIKAN DAN KEBUDAYAAN DALAM MEMPROMOSIKAN MUSEUM TUANKU IMAM BONJOL SEBAGAI DESTINASI WISATA SEJARAH DI KABUPATEN PASAMAN - Mufeldo Prakasa Nenggala; Muhammad Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Tuanku Imam Bonjol Museum is one of the places visited by many tourists because it has good and strong potential and attraction to attract tourists so that this historical tourist attraction is prioritized in its development and as a mainstay of tourist attraction in Pasaman Regency. So the author is interested in conducting a research entitled "Tourism Communications Education and Culture Departement in Promoting the Tuanku Imam Bonjol Museum as a Historical Tourism Destination in Pasaman Regency."This study uses a qualitative descriptive type of research. The research subjects here consist of seven people, where the subject is directly related to promoting the Tuanku Imam Bonjol Museum. This study uses data collection techniques through interviews, observation and documentation. Researchers use data analysis methods Miles & Huberman analysis consists of three streams of activities that occur simultaneously, namely: data reduction, data presentation, conclusion drawing/verification. To achieve the validity of the data in this study, the authors used extension of participation and triangulation.The results showed that, the first source was the Department of Education and Culture of Pasaman Regency. And second, the message contains persuasive, informative and educational. The three channels (Media) are print media and the use of Facebook as social media. The four receivers are targeting elementary-high school students and are open to the general public of Pasaman and from outside Pasaman. Fifth, we can see the obstacles in promoting the Tuanku Imam Bonjol museum, only the development of the use of social media in promoting and the wider spread of the Covid-19 virus.